Analysis study of some Biokinematic variables for Iraqian senior Breaststroke swimmers and its relationship with performance - Mansour, Samir (Journal of Physical Education, 2011)
The study has been analysis some Biokinematic variables for Iraqian senior Breaststroke swimmers .in order to develop performance . The sample of the study was four Iraqian Champion Breaststroke swimmers . The researcher has used the descriptive design to resolve the problems . The study has come the some following conclusions ;  The study has exist more glide by hands forword and backward to excess longitude stroke to improve performance .  The study has exist lack forward speed through collected elbows .  The study has exist the longitude of stroke is more important than repeated . The researcher recommends some of the following ;  There is necessity to use Biokinematic analysis to determine technical mistake in Breaststroke swimming .  The researcher recommend to supply coaches with Biokinematic analysis results before they putting there training porgrammes to avoid mistake .  Perform more similar studies on another Biokinematic variables of Breaststroke swimming